Computing the ultrafast and radiationless electronic excited state decay of cytosine and 5methylcytosine cations: uncovering the role of dynamic electron correlation - Segarra-Marti,J; Tran,T; Bearpark,M (ChemPhotoChem, 2019)
Photoionisation in DNA, i.e. the process of photoinduced electron removal from the chromophoric species − the nucleobases − leading to their cationic form, has been scarcely studied despite being considered to be responsible for significant damaging instances in our genetic material. In this contribution we theoretically characterise the electronic ground and excited state decay pathways of cationic DNA nucleobase cytosine+ and its epigenetic derivative 5methylcytosine+, including the effects of dynamic electron correlation on energies and geometries of minima and conical intersections. We do this by comparing the results of XMSCASPT2 calculations with CASSCF estimates and we find some significant differences between the results of these two methods. In particular, including dynamic electron correlation is found to significantly reduce the barrier to access the (D1/D0) conical intersection. We find notable similarities in both cytosine and 5methylcytosine cations, accessible conical intersections in the vicinity of the FranckCondon region are found. This points towards an ultrafast depopulation of their electronic excited states. Moreover, the shape of the ground state potential energy surface strongly directs the decaying excited state population towards the cationic ground state minimum on ultrafast timescales, preventing photofragmentation and thus explaining their photostability.